If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -45 = 44 Reorder the terms: -45 + x = 44 Solving -45 + x = 44 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '45' to each side of the equation. -45 + 45 + x = 44 + 45 Combine like terms: -45 + 45 = 0 0 + x = 44 + 45 x = 44 + 45 Combine like terms: 44 + 45 = 89 x = 89 Simplifying x = 89
| 6+7x=19+2x | | 9m-5=10+4m | | 5[2x-1]=15 | | 7p-28=-70+p | | 8x+5y-10xy= | | -25=x+8 | | 7z=-42 | | (x+5)2-81=0 | | 10x+4=3x+67 | | -3x-7x=-40 | | -54=9r+3-12+3r | | 10x=9x-31 | | 2((2x-12)+x)=96 | | -6x-22=-124 | | (x+2)/7=(x-1)/5 | | -62=4*6x | | -5+9= | | 4-10x=12x-7 | | 5(10-j)=3j+2 | | 9-10(n)=1 | | 3x+5y=-21 | | 7x^2-28x+15=0 | | 3(n)=50+n | | 5x^2+6x-1=0 | | 8x-(4x+6)=26 | | 141-7x=38x+16 | | (3x+5)/8=(2x-4)/3 | | v^2=10-3v | | s^2=54-3s | | 5t-30=15 | | 5y^2+30y+40=0 | | 6-4x=6x-8x-4 |